Six HLA-D region alpha-chain genes on human chromosome 6: polymorphisms and associations of DC alpha-related sequences with DR types. - Spielman, R S (1984)
Analysis of cosmid clones containing genes related to the HLA-DR alpha chain calls for at least six HLA-D region alpha-chain coding sequences in man; namely, DR alpha, DC alpha, DX alpha (very closely related to DC alpha), SB alpha 1, SB alpha 2 (two closely linked genes on the same cosmid clones), and DZ alpha. The first four genes have been described previously. SB alpha 2 and DZ alpha are recently identified genes, characterized by their unique and, from a limited study, nonpolymorphic bands when used as probes for human DNA on Southern blots. All of the genes are present in somatic cell hybrids containing a human X/6 translocation chromosome, and so they are all presumably in the HLA region. The polymorphisms in the region of the DC alpha and related DX alpha genes were studied with Southern blots of DNA from a set of mostly homozygous HLA-D-typing cell lines. With EcoRI, the band patterns for the DC alpha gene corresponded to the major cross-reactive HLA-DR serotypes associated with DC (namely MT1, -2, and -3) while the DX alpha band was invariant. Both genes were polymorphic with the enzyme Taq I. Within some DR types additional polymorphic variation was detected at the DNA level, implying the existence of subtypes. The pattern of polymorphisms for DC alpha, and to a lesser extent for DX alpha, suggests that these genes may play an important role in certain HLA-D associations with disease.